Cell-based assays in flowing and sessile drops - Prastowo, A (2018)
Cell-based assays have been performed in aqueous drops within a bulk immiscible fluid phase, as an alternative to multi-titer plates. Many microfluidic functions have been developed to manipulate these drops, for example, to merge pairs of drops, and sort drops based on size or fluorescence they emit. Whilst these functions have been successfully demonstrated in the proof-of-principle stage, challenges remain in combining them into one working platform for real-life applications. As many microfluidic devices are designed for only one specific application, adjustments are required to perform different tasks. For applications involving cell culture, one must be mindful that cells are subjected to a very different environment in microfluidic devices compared to conventional culture. Small culture volume results in large surface-to-volume ratio which would affect transport of molecules within the drops and with the interfaces. Furthermore, materials used in many microfluidic devices are usually different from those used in conventional culture. Motivated by these challenges, here a passive drop merging method in a single Teflon tube and a liquid handling method using sessile drops on a Petri dish are developed. Biocompatibility of these methods for cell-based assays are assessed using mammalian cells. The first method uses fluid mechanics of three or more immiscible fluids to control the relative speed of individual drops, rather than complex channel geometries. Fluids and surfactants were screened to find a biocompatible combination for this method. The second method concerns performing cell-based assays in sessile drops, overlaid with FC-40, on tissue-culture-treated polystyrene dishes. The impact of this arrangement on cells, and the alternation of the pinning line/interface by Fetal Bovine Serum (FBS) is examined in some details. It is found that constituents of FBS accumulate at the interface which results in an alternation on the pinning line properties that is beneficial to such assays.